Could the thorax CT protocol be designed based on neck circumference? (Annals of Medical Research, 2021)
Aim: To evaluate whether neck circumference (NC) is an appropriate somatometric parameter for determining tube voltage of thorax CT for avoiding unnecessary radiation dose.Matetial and Methods: One hundred sixty-three patients who underwent unenhanced thorax CT were included in the study. The NC, body weight and height were measured and the body mass index (BMI) was calculated. The patients were divided into two groups before CT examination: In group 1, the different kV values based on neck circumferences were used on CT protocol, however the same kV value was used for all patients in group 2. Both group CT images were evaluated visually and numerically.Results: The effective dose showing radiation received by the patient was lower in Group 1 than the Group 2 (p0.001). However, the aorta noise value as reducing the image quality was higher in Group 1 (p0.001). The visual image quality score was lower in group 1 than group 2 (p=0.002).Conclusion: Even though some clinical studies focus on the NC which reflects the thorax fat tissue, our study concludes that it is not a suitable anthropometric parameter in designing an individual-specific dose protocol for thorax CT.Keywords: Individual dose control; computed tomography; ALARA; tube voltage; neck circumference; body mass index.